PENGARUH BEBAN KERJA DAN BURNOUT (KEJENUHAN KERJA) TERHADAP INTENSI TURNOVER GURU SEKOLAH MENENGAH PERTAMA DI SEKOLAH BERCIRIKAN AGAMA BUDDHA DI DKI JAKARTA - Widia Darma (Jurnal Manajemen Pendidikan, 2018)
The objective of the research is find out the effet of workload and burnout on the teacher’s intention turnover.the research was conducted at Buddhist junior high school in Jakarta. The research was using a survey method with path analysis applied in the hypothesis and 92 sample selected by simple random sampling. The research techniques is analysis with quantitative research approaches by using causal analysis. The finding of the research are: 1) there is a positive direct effect of workload on turnover intention; 2) there is a positive direct effect of burnout on turnover intention; 3) there is a positive direct effect of workload on burnout.